Party, State and the Control of Information in the Lao People’s Democratic Republic: Secrecy, Falsification and Denial - Ian G. Baird (2018)
© 2018 Journal of Contemporary Asia Since taking control of Laos in 1975, the Lao People’s Revolutionary Party and the government of the Lao People’s Democratic Republic (Lao PDR) have relied heavily on secrecy, denial and information management and control to govern. These tools have been used for presenting the Party and state as united in support of the country’s one-party communist political system and as being the only real political option. This article presents a number of examples of the particular ways the Party and state have done this. The following are discussed: the little-known rift between the “Red Prince” Chao Souphanouvong and Kaysone Phomvihane; conflict between the Lao PDR and Vietnam and China; the anti-Lao PDR insurgency; calls for political change via the “Social Democratic Club” in 1990; unsuccessful student protests for political change in 1999 and 2009; the forced disappearance of Sombath Somphone; and recent attempts to control social media to publicise anti-government viewpoints. Secrecy, falsification and information management and control have important implications, both with regard to conducting research about Laos and in relation to how outsiders tend to analytically frame the study of Party and state.